Inimigos naturais na restauração florestal - Ferreira, Rafael Borrasca (2017)
Forest restoration is a global priority by make the reestablishment of ecosystem services. Many of these services have major importance on the agriculture fields, such as the pest control given by the predators and parasitoids fauna. In the search for a better understanding of the relation between natural pest control and the forest restoration, we aimed to: i) verify if the restoration process can increase the abundance, richness and diversity of natural enemies; ii) verify if these increases are exclusive to natural enemies or occurs with others arthropods; iii) compare attributes from the vegetation structure and the natural enemies community. The study was carried out in two different landscapes in São Paulo state, Araras and Itu. In each landscape, we selected a pasture, a younger, an intermediate and an older restoration planting, and a forest fragment. In September and October of 2016, five plots of 10x10m we replaced in each area for measuring tree density, sapling density and canopy cover. A pitfall trap was placed in the center of each plot for the passive arthropod survey and we used the beat sheet in the four trees nearest to the center of the plot for an active arthropod survey, we performed these surveys two times, one in the dry and the other in the rainy seasons. The richness and diversity of natural enemies enhanced by the process of restoration, and this enhance was higher for natural enemies than to arthropods in general. The abundance of natural enemies of restoration sites shows no difference to pastures and forest patches, but pasture shows less abundance than the forest, we didn’t found difference in the abundance of natural enemies and the other arthropods though this restoration chrono sequence. Canopy cover and tree densities were positively correlated to richness, diversity and abundance of natural enemies, showing that the forest structure reestablishment in the restoration areas can enhance the natural enemies community.